2002
DOI: 10.1073/pnas.162371799
|View full text |Cite
|
Sign up to set email alerts
|

The essential role of Cited2, a negative regulator for HIF-1α, in heart development and neurulation

Abstract: Cited2 is a cAMP-responsive element-binding protein (CBP)͞p300 interacting transcriptional modulator and a proposed negative regulator for hypoxia-inducible factor (HIF)-1␣ through its competitive binding with HIF-1␣ to CBP͞p300. Disruption of the gene encoding Cited2 is embryonic lethal because of defects in the development of heart and neural tube. Morphological and Doppler echocardiographic analyses of Cited2 ؊/؊ embryos reveal severe cardiovascular abnormalities, including pulmonic arterial stenosis and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
210
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(215 citation statements)
references
References 30 publications
5
210
0
Order By: Relevance
“…CITED2 is activated by hypoxia by HIF-1 itself, providing an additional layer of HIF-1 autoregulation by controlling HIF-1 ␣ access to CBP/p300, and therefore limiting HIF-1-dependent hypoxic response. Inactivation of HIF-1 target genes in CITED2 knockout mice seems to support the role of CITED2 as a HIF-1 competitor (20). Similar to PHD2 and FIH, CITED2 activation by hypoxia might indicate a role for this molecule in the rapid inactivation of the hypoxic response upon reoxygenation.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…CITED2 is activated by hypoxia by HIF-1 itself, providing an additional layer of HIF-1 autoregulation by controlling HIF-1 ␣ access to CBP/p300, and therefore limiting HIF-1-dependent hypoxic response. Inactivation of HIF-1 target genes in CITED2 knockout mice seems to support the role of CITED2 as a HIF-1 competitor (20). Similar to PHD2 and FIH, CITED2 activation by hypoxia might indicate a role for this molecule in the rapid inactivation of the hypoxic response upon reoxygenation.…”
mentioning
confidence: 73%
“…Similar to PHD2 and FIH, CITED2 activation by hypoxia might indicate a role for this molecule in the rapid inactivation of the hypoxic response upon reoxygenation. CITED2 may play a role in heart morphogenesis and the establishment of left-right asymmetry in the early embryo (20)(21)(22).…”
mentioning
confidence: 99%
“…MCF-10A was provided by Dr Amy Wilson-Delfosse (Case Western Reserve University). Primary MEF cultures were harvested and maintained as described (Yin et al, 2002). For generation of MEF cell lines, primary MEFs were immortalized by retroviral infection with a retroviral vector containing simian virus 40 LT antigen (Williams et al, 1988), provided by Dr David Williams (University of Cincinnati).…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
“…This is supported by the observation that hypoxia induces Cited2 expression. Elevated level of Cited2 then functions to downregulate hypoxia inducible factor (HIF)-1-driven transcription by competing with HIF-1a for binding to CBP/p300 Yin et al, 2002;Freedman et al, 2003). We and others have shown that disruption of the gene encoding Cited2 is embryonic lethal and causes defects in the development of heart and neural tube (Bamforth et al, 2001;Barbera et al, 2002;Yin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CITED2 acts as a repressor for hypoxia-inducible factor 1␣, (HIF1A), which in turn regulates important growth-regulatory target genes like VEGF, Glut1(SLC2A1) and phosphoglycerate kinase (PGK1). 45 …”
Section: Differentiation-related Genes Specific For Ewsmentioning
confidence: 99%